Challenges in achieving the UNAIDS 95-95-95 targets: evaluation of the antiretroviral therapy program among adult HIV/AIDS patients at Woldia General Hospital, Northeast Ethiopia - Seid, Seada; Yitayal, Mezgebu; Yazachew, Lake; Arega, Abdurahman; Dessie, Tilahun; Yesuf, Hassen Ahmed; Hassen, Jemila Seid; Kassaw, Abdulaziz Kebede; Yimer, Ali (Frontiers in Public Health, 2025)
BackgroundIn Ethiopia and other resource-limited settings, antiretroviral therapy (ART) has been instrumental in reducing the harmful impact of the HIV pandemic. ART program aims to decrease morbidity and mortality, minimize healthcare costs, and enhance the quality of life for individuals living with HIV. However, the program faces several challenges, including poor medication adherence, a higher incidence of adverse effects, drug resistance, and persistent issues of discrimination and stigma. This study aimed to evaluate the implementation process of the antiretroviral therapy (ART) program among adult HIV/AIDS patients at Woldia General Hospital in Northeast Ethiopia.MethodsBetween June 1 and June 30, 2020, a mixed-method case study was conducted. A total of 384 patient charts were reviewed, and 402 individuals living with HIV/AIDS were interviewed using systematic random sampling technique and interviewer administered questionnaire. Additionally, six key informant interviews were conducted, and 30 observations of healthcare professionals were recorded. The quantitative data were entered into Epidata version 4.6 and subsequently transferred to STATA version 14 for analysis. Bivariable analysis was performed to identify variables with p-values less than 0.2 as potential candidates for multivariable logistic regression, with statistical significance set at p < 0.05. The qualitative data underwent transcription, translation into English, coding, thematic analysis, and manual interpretation. The overall implementation status of the program was assessed based on predefined evaluation criteria.ResultsAccording to national guidelines, 74.8% of the program was implemented consistently. Patient satisfaction was reported at 77%, healthcare personnel adherence to guidelines at 66%, and resource availability at 88.4%. Key challenges included shortages of test kits, Plumpy’Nut, and medications for opportunistic infections, as well as inadequate data management and issues with patient file handling. Most laboratory tests were not done according to the national guidelines. Additionally, refreshment training for health care providers was not given. Factors associated with patient satisfaction included the ability to disclose their condition (AOR = 3.25; 95% CI: 1.46, 7.26) and a waiting time of less than 30 min (AOR = 3.88; 95% CI: 1.26, 11.97).ConclusionThe overall level of program implementation was very good. However, patient satisfaction did not meet the national target of 85%, and adherence to national guidelines was minimal. Essential supplies such as HIV test kits, Plumpy’Nut, viral load tests, and medications for opportunistic infections were not consistently available. Additionally, most laboratory tests were not conducted in accordance with the guidelines. Factors associated with patient satisfaction included the ability to disclose HIV status and waiting times of under 30 min.